Endocarditis caused by Actinobacillus actinomycetemcomitans. - Schack, S H (1984)
Actinobacillus actinomycetemcomitans is a gram-negative coccobacillus which is a very rare cause of bacterial endocarditis. Preexisting cardiac lesions are a main contributing factor, and antibiotic prophylaxis has long been felt necessary before dental or other manipulation to prevent endocarditis. Penicillin in combination with an aminoglycoside has been the most often used treatment regimen. We present a case of endocarditis caused by this organism which developed after antibiotic prophylaxis for dental cleaning. Streptomycin and rifampin therapy resulted in the cure of the infection. The treatment and epidemiology of Actinobacillus endocarditis are reviewed.